2016
DOI: 10.1136/thoraxjnl-2015-207402
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and tissue destruction in pulmonary TB

Abstract: BackgroundIt is unknown whether lesions in human TB are hypoxic or whether this influences disease pathology. Human TB is characterised by extensive lung destruction driven by host matrix metalloproteinases (MMPs), particularly collagenases such as matrix metalloproteinase-1 (MMP-1).MethodsWe investigated tissue hypoxia in five patients with PET imaging using the tracer [18F]-fluoromisonidazole ([18F]FMISO) and by immunohistochemistry. We studied the regulation of MMP secretion in primary human cell culture mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 35 publications
3
132
1
3
Order By: Relevance
“…During pulmonary TB disease in humans, the presence of caseum-filled hypoxic necrotic granulomas in the lungs is associated with severe disease, facilitating bacterial spread and compromising lung integrity. Human pulmonary TB lesions are hypoxic (5), and as a result, matrix metalloproteases such as MMP-1 associated with tissue remodeling are upregulated (5). Previous studies have shown that animal models of TB (e.g., rabbit, guinea pig, and nonhuman primate) develop heterogeneous granulomas, wherein hypoxia is closely associated with necrotic granulomas as opposed to solid granulomas (6).…”
Section: Introductionmentioning
confidence: 99%
“…During pulmonary TB disease in humans, the presence of caseum-filled hypoxic necrotic granulomas in the lungs is associated with severe disease, facilitating bacterial spread and compromising lung integrity. Human pulmonary TB lesions are hypoxic (5), and as a result, matrix metalloproteases such as MMP-1 associated with tissue remodeling are upregulated (5). Previous studies have shown that animal models of TB (e.g., rabbit, guinea pig, and nonhuman primate) develop heterogeneous granulomas, wherein hypoxia is closely associated with necrotic granulomas as opposed to solid granulomas (6).…”
Section: Introductionmentioning
confidence: 99%
“…Professor Friedland's group (London) used positron emission tomography (PET) scans with the hypoxic-specific tracer ( 18 F-labelled fluoromisonidazole), to show for the first time that pulmonary TB lesions are severely hypoxic and that hypoxia upregulates the collagenase matrix metalloproteinase-1, an important contributor to the cavitation and lung destruction seen in this disease 7. This was followed by Professor Lederer (New York, USA), who showed that higher levels of rheumatoid arthritis (RA) autoantibodies, even in the absence of clinically evident RA, are associated with subclinical interstitial lung disease (ILD) on CT imaging, particularly in smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced pulmonary TB is characterised by tissue destruction, hypoxia and cavitation,9 with high bacterial loads within the cavity wall,10 whereas pleural TB has a relatively low bacterial load with extensive fluid collection 11. Consequently, pleural fluid culture is positive in fewer than 50% of cases 12.…”
mentioning
confidence: 99%